1991
DOI: 10.1093/jac/28.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Low dose intraperitoneal ciprofloxacin for the treatment of peritonitis in patients receiving continuous ambulatory peritoneal dialysis (CAPD)

Abstract: Ciprofloxacin at a dose of 25 mg/L of dialysate was administered intraperitoneally for five days as a single agent for the empirical treatment of CAPD peritonitis. One hundred and seventeen consecutive episodes of peritonitis occurred in 65 patients during the study period, and 100 episodes were entered in the study. This therapy was successful in 79% of episodes. Resistant organisms (MIC greater than 4 mg/L) all of them coagulase-negative staphylococci, were isolated in nine (7.8%) of the 117 episodes. Mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There is now ample experience in the use of quinolones for the treatment of PD-related peritonitis. Ciprofloxacin has been reported on most frequently (9-14,18,20-25) but other related drugs, including ofloxacin, levofloxacin, and pefloxacin, have also been used in this setting (15-17). Quinolones have been used alone and in association with other antimicrobials, and both oral and IP routes have been employed successfully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now ample experience in the use of quinolones for the treatment of PD-related peritonitis. Ciprofloxacin has been reported on most frequently (9-14,18,20-25) but other related drugs, including ofloxacin, levofloxacin, and pefloxacin, have also been used in this setting (15-17). Quinolones have been used alone and in association with other antimicrobials, and both oral and IP routes have been employed successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Older quinolones [including ciprofloxacin (Cpx)] have demonstrated an equilibrated activity against gram-positive and gram-negative bacteria (including Pseudomonas aeruginosa), while newer quinolones show improved activity against gram-positives, Chlamydia spp, Mycoplasma spp, mycobacteria, and selected anaerobes (8). Oral and intraperitoneal (IP) quinolones have been extensively used for the management of PD-related peritonitis, with overall satisfactory results (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, and similarly to other antibiotics, development of bacterial resistance may compromise the long-term results of this family of antimicrobials.…”
Section: Treatment Of Peritonitis and Exit-site Infectionsmentioning
confidence: 99%
“…An interesting historic review on the use of fluoroquinolones in PD-related peritonitis was published by Janknegt in 1991 (20). Some studies show that ciprofloxacin is not effective in treating CAPD-and APD-related peritonitis (21)(22)(23); other studies have demonstrated that ciprofloxacin may be successful in this setting (18,(24)(25)(26)(27). Yeung et al (28) have shown that ciprofloxacin, given 750 mg orally every 12 hours to continuous cyclic PD patients, may be useful for empirical gram-negative coverage and for the treatment of documented peritonitis caused by sensitive E. coli or Klebsiella species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with ciprofioxacin in chronic ambulatory peritoneal dialysis (CAPD) patients were mostly performed using intraperitoneally administered ciprofioxacin at a dose of 25 or 50mg/1 for each bag of dialysate for 5-7 days (LUDLAM et al 1990;DRYDEN et al 1991;PEREZ et al 1993). Cure rates for gram-negative infections were higher (95%) than for gram-positive infections (67%).…”
Section: Peritonitis In Chronic Ambulatory Dialysis Patientsmentioning
confidence: 99%